2016
DOI: 10.1080/08870446.2016.1204450
|View full text |Cite
|
Sign up to set email alerts
|

The burden of filial piety: A qualitative study on caregiving motivations amongst family caregivers of patients with cancer in Singapore

Abstract: In Singapore and Asia, sociocultural values of family caregiving are not uniformly experienced as positive, and may be burdensome for caregivers who give care primarily for extrinsic motivations. As family caregiving needs increase, targeted psychosocial support for caregivers with less autonomous behavioural orientations may pre-empt caregiver burnout and burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 40 publications
1
107
1
2
Order By: Relevance
“…All studies included here lent insight to the situational demands that influenced adult caregivers' motivation for providing care to a friend or relative with a long‐term illness. Most of the studies had investigated caregivers' quality of motivation and classified it according to different constructs in SDT such as intrinsic motivation, identified motivation, introjected motivation, external motivation and amotivation . In these studies, SDT terminology has been used to identify, measure, classify, categorise or describe caregivers' quality of motivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies included here lent insight to the situational demands that influenced adult caregivers' motivation for providing care to a friend or relative with a long‐term illness. Most of the studies had investigated caregivers' quality of motivation and classified it according to different constructs in SDT such as intrinsic motivation, identified motivation, introjected motivation, external motivation and amotivation . In these studies, SDT terminology has been used to identify, measure, classify, categorise or describe caregivers' quality of motivation.…”
Section: Resultsmentioning
confidence: 99%
“…helping because you enjoy/value this behaviour and experience volition and choice), or controlled motivation, understood as extrinsic motivation (i.e. helping because you believe you should) . One qualitative study reported that in real life, the constructs and categories of motivation are more ambiguous than, and not as easy to identify as, in the theory .…”
Section: Resultsmentioning
confidence: 99%
“…Due to an ageing population in Singapore, the number of older people needing caregiving assistance in at least one activities of daily living (ADLs) is estimated to increase from 31,738 in 2010 to 82,968 in 2030 (Thompson et al, 2014). As care delivery to older people shifts from institutions to the community, families are expected to take on the caregiving role to fulfil societal expectations like filial piety (Ng, Griva, Lim, Tan, & Mahendran, 2016;Yeoh & Huang, 2010). Traditionally, caregiving responsibilities were the responsibilities of females of the family.…”
Section: Introductionmentioning
confidence: 99%
“…Singaporean society was built upon Confucianism principles, with an emphasis on filial piety [6,7]. Hence, the family is the first line of support for patients with family members expected to take on the role of informal caregiving [8].…”
Section: Introductionmentioning
confidence: 99%